The Moderating Role of Information Quality in The Relationship Between Operational Performance and Supply Chain Integration: Evidence from The Manufacturing Sector - Mohammad Kanan (Decision Making: Applications in Management and Engineering, 2024)
In this study examined the moderating effect of information quality (InfoQ) in the relationship between supply chain integration (SCI) and operational effectiveness within the manufacturing sector. Respondents from selected manufacturing companies provided the study data, which were then analyzed using structural equation modeling, to ascertain the proposed relationships. Results affirmed a correlation between SCI (both supplier and customer integration) and operational effectiveness, denoting the ability of streamlined supply chains in increasing operational outcomes. This correlation is also influenced by InfoQ, which means that integrated supply chains require accurate information. Supply chain management can be understood better through the study findings. Also, the findings could facilitate managers in improving their operational performance through the use of SCI-based initiatives.